PREDICTING REPURCHASE INTENTION WITH E-SATISFACTION AS A MEDIATOR ON E-COMMERCE SHOPEE - Darmawi, Michelle; Ruslim, Tommy Setiawan (Graduate Program of Universitas Tarumanagara, 2024)
This study aims to examine the effect for Shopee (one of Indonesia’s e-commerce service) of web design that contains visual and user interface, information quality that dense, clear and relevant, as well as safe, on-time delivery services and an assortment of delivery services on repurchase intention with e-satisfaction as a mediating variable. Nowadays, problems often arise from consumer talk about web design, user interfaces that are not too familiar with everyday use. Data collection in this study uses non-probability sampling with range of the shopee (e-commerce) buyer in Jakarta only, with the type of that sample that may be a purposive sampling. The number of samples in this study were 223 respondents. This study uses Smart PLS-SEM version 4.0 to process data. The purpose of this research is to provide insight for future research and prove that it can increase customer satisfaction and increase repurchases in shopping.. Using several leading theories and conceptual variables, the variables that become this study are more valid and can be considered for future research. and linking between important elements, namely information quality, delivery service, e-satisfaction, web desig, information quality with repurchase intention. Based on the results of this study indicate that web design, information quality, and delivery service can significantly and positively influence repurchase intention mediated by e-satisfaction.